2007
DOI: 10.1063/1.2743402
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic current gain cutoff frequency of 30GHz with carbon nanotube transistors

Abstract: High frequency capabilities of carbon nanotube field-effect transistors (CNTFETs) are investigated. Structures with a large number of single-walled carbon nanotubes were fabricated using dielecrophoresis to increase the density of nanotubes in the device channel. The authors obtained an intrinsic current gain cutoff frequency of 30GHz establishing state-of-the-art high frequency (hf) potentialities of CNTFETs. The device also showed a maximum stable gain above 10dB at 20GHz. Finally, the parameters of an equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 17 publications
2
67
1
Order By: Relevance
“…High cut-off frequency is essential to realize the high-speed response of devices. Recent experimental works have demonstrated the cut-off frequencies up to 50 GHz using the CNT-FETs with a few hundred nanometers channel length, [60][61][62][63][64] and the phenomenological law has been also obtained. 65 Although the cut-off frequency of CNT-FET with a 2 nm gate is estimated to reach as high as 1.6 THz using the nonequilibrium Green's-function method, 66 the length dependence of the cut-off frequency from the ballistic to diffusive regimes has not been clarified yet theoretically.…”
Section: Length Dependence Of Mobility and Cut-off Frequencymentioning
confidence: 99%
“…High cut-off frequency is essential to realize the high-speed response of devices. Recent experimental works have demonstrated the cut-off frequencies up to 50 GHz using the CNT-FETs with a few hundred nanometers channel length, [60][61][62][63][64] and the phenomenological law has been also obtained. 65 Although the cut-off frequency of CNT-FET with a 2 nm gate is estimated to reach as high as 1.6 THz using the nonequilibrium Green's-function method, 66 the length dependence of the cut-off frequency from the ballistic to diffusive regimes has not been clarified yet theoretically.…”
Section: Length Dependence Of Mobility and Cut-off Frequencymentioning
confidence: 99%
“…Applying charge-control theory [10] to FETs, the overall, source-drain signal delay time relates to , and to the change in input charge that is required to bring about a change in output current (1) where, for a FET, is the change in charge on the gate, and is the change in drain current. Here, we consider the changes in charge and current due to a change in gate-source voltage .…”
Section: A Derivation Of Delay Timementioning
confidence: 99%
“…T HE SMALL size, unusual topography, and technological immaturity of carbon nanotube field-effect transistors (CNFETs) have contributed, no doubt, to the fact that the present record for their measured unity-current-gain frequency is a modest 30 GHz [1]. For the moment, then, we need to rely on simulations to get a better idea of the high-frequency capability of CNFETs.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, several field-effect transistors based upon individual nanotubes, operating in the low GHz range have been achieved [155][156][157][158][159][160][161][162][163]. However intrinsic cutoff frequencies in the THz regime have yet to be realized.…”
Section: Thz Transistorsmentioning
confidence: 99%
“…The performance of such devices have been limited by parasitic effects and impedance mismatches. One approach to increase the extrinsic cutoff frequency is to utilize networks or arrays of aligned nanotubes [158,[164][165][166][167][168][169][170][171][172][173]. Most recently, Che et al [174] demonstrated that such an array of carbon nanotube transistors can achieve an extrinsic current-gain cutoff frequency of 25 GHz.…”
Section: Thz Transistorsmentioning
confidence: 99%